Biokinematic Analysis of Specific Variables of the Overhead Smash Skill and Its Correlation to Performance Accuracy in Tennis - Oday Mahdi Hadi (Eximia, 2025)
Around the world, a few nations have begun to use organized planning. They are utilizing applied sciences to enhance performance levels in various sports. Meanwhile, competition among these nations has intensified to innovate modern scientific methods. Additionally, there is a focus on conducting studies and research, as well as addressing the fundamental factors involved in executing skillful performances to discover new training methods. Furthermore, attention is being given to the physical and psychological aspects specific to each sport, along with mechanical factors. This development has led to rapid advancements, significantly contributing to the evolution of different sports. All human and scientific disciplines are utilized in this development, including biomechanics, which employs kinematic analysis to perform a variety of tasks, for instance: (analysis, clarification, reasoning, improvement, findings, suggestions, and technique development). Consequently, this is regarded as one of the core biomechanical techniques. The process allows for the breakdown of a movement into its constituent parts according to the chosen categorization type. It then determines the characteristics of each component so that the appropriate mechanical laws and principles can be applied for the movement's optimal execution. The aim of the study is to establish a correlation between the values of certain biomechanical characteristics related to the overhead press skill and tennis performance accuracy. The researcher employed a descriptive methodology, with a sample consisting of three players from the youth category. Additionally, the researcher used scientific technical observation, measurement, analysis, and testing as means to collect data on certain biomechanical variables. To achieve scientific technical observation, video recording was utilized. The researcher concluded that there is a difference in the values of the biomechanical variables related to the motor performance of the overhead press skill among the research sample and across different stages of the movement.